Distinct creep regimes of methane hydrates predicted by a monatomic water model - Henrik Andersen Sveinsson; Pinqiang Cao (Physical Review Research)
The power-law creep properties of methane hydrates were measured experimentally two decades ago, but their microscopic explanation is still missing. Here we show, using molecular dynamics simulations spanning almost 2 orders of magnitude of stresses and 3 orders of magnitude of strain rates, that such power-law creep emerges in molecular dynamics simulations of polycrystalline methane hydrates using a monatomic water model, suggesting that only simplified molecular interactions and the concept of a hydrate polycrystal are needed for such power-law creep behavior to emerge. Damage patterns post-creep suggest that hydrates are strong because damage only occurs on crystal surfaces.